Examine the Women Communication Managerial Skill at PT LAZ Coal Indonesia - Dedy Gunawan; Nurannafi Farni Syam Maella; Sanhari Prawiradiredja; Citra Rani Angga Riswari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Efficient communication plays a crucial role in effective management, especially in the coal mining industry. This industry requires strong interpersonal and leadership skills due to its intricate stakeholder relationships and demanding operational environments. This case study explores the communication-based managerial skills of women leaders at PT LAZ Coal Indonesia, a well-known coal mining company in the region. The study follows the methodological approach of Robert K. Yin. The existing literature on communication in the mining industry emphasizes the significance of strategic communication in effectively managing intricate stakeholder dynamics, promoting teamwork, and facilitating organizational transformation. Research has highlighted the specific communication obstacles that women encounter in industries dominated by men. These challenges include overcoming gender biases and establishing credibility. This qualitative case study utilized in-depth interviews with a purposive sample of two women managers at PT LAZ Coal Indonesia, encompassing mid-level supervisors to senior executives. The interviews delved into the participants' communication strategies, leadership approaches, and experiences in navigating the organizational culture. In addition, the researchers observed the women managers in their work environments and analyzed company documents to cross-reference the data. The research uncovers that the female managers at PT LAZ Coal Indonesia have honed a variety of communication-focused managerial abilities, such as attentive listening, compassionate issue resolution, and the tactical utilization of both formal and informal communication avenues. These skills have allowed them to establish trust with their teams, efficiently handle stakeholder relationships, and bring about organizational change. Nevertheless, the women encountered obstacles, including the task of maneuvering through gender-based biases and the requirement to adjust their communication styles to fit into the predominantly male organizational culture. This study offers valuable insights into the communication-based managerial skills of women leaders in the coal mining industry, showcasing their adeptness in navigating intricate organizational dynamics and cultivating collaborative work environments. The findings could potentially shape the creation of training and mentorship programs for women who aspire to be leaders. Additionally, they could add to our knowledge of communication strategies based on gender in industries that are predominantly male-dominated.